Molecular Markers: New Prospects in Plant Genome Analysis - Sharma, A.; Namdeo, Ajay G.; Mahadik, K.R. (Pharmacognosy Reviews)
Accurate authentication is constantly necessary to prevent the adulteration of target plant with other plant species. For the standardization of botanical preparations chromatographic techniques (HPLC, TLC, HPTLC, UV spectroscopy, mass spectroscopy, gas chromatography, infrared and NMR spectroscopy) have limitations because the compositions and relative amount of chemicals in a species varies with growing conditions, harvesting periods, post-harvest processes and storage conditions. This can be misleading if the samples are deliberately adulterated with a marker compound. Also, it is difficult to distinguish closely related species due to similar chemical compounds. Ordinary chemical authentication was not reliable enough to produce easyto-interpret results. Therefore, it is necessary to develop a more effective, accurate, reliable and sensitive technology for the authentication of herbs. In recent years DNA manipulation techniques have been adapted for the authentication of herbs which comprise of the molecular markers, sequencing of specific genes, and sophisticated hybridization setups such as DNA microarrays. DNA-based molecular markers have acted as resourceful tools in various fields like taxonomy, physiology, embryology, plant breeding, ecology, genetic engineering etc. The innovation of polymerase chain reaction was a milestone in the development of DNA markers. This facilitated the development of marker based gene tags, cloning of agronomically important genes, variability studies, phylogenetic analysis, selection of wanted genotypes, etc. Thus DNA markers offer several advantages over conventional phenotypic markers, as they provide data that can be analyzed objectively.
Keywords: Molecular authentification; DNA markers; Polymerase chain reaction; RAPD